Pleomorphic Adenoma of the Cheek: Case Report and Literature Review - Avagnina, Andrea; Schiraldi, Luigi; Dalaqua, Mariana; Yerly, Stéphane; Morrison, Miranda; Hallak, Bassel; Bouayed, Salim (Archives of Clinical and Medical Case Reports, 2020)
A 56-year-old man, with good general health, was addressed by his own physician to our ENT and cervico-facial surgery department with a chief complaint of a mass in the right check. The mass has been progressively growing over the last 15 years, and has become increasingly troublesome in the last 3 months. MRI imaging suggested a vascular malformation. Patient underwent an “en-bloc” surgical excision of the mass, which revealed a pleomorphic adenoma. Pleomorphic adenomas are benin neoplasms composed of mesenchimal and epithelial components. They most frequently occur in the major salivary glands. Ectopic localisations are very rare. Here we report a case of an ectopic pleomorphic adenoma in the subcutaneous layer of the cheek and a literature review. <gdiv></gdiv>